PERDAGANGAN ANAK SEBAGAI BENTUK PELANGGARAN HAK-HAK ANAK - Yanuar Farida Wismayanti (Politeknik Kesejahteraan Sosial, 2009)
Children have a very high risk of trafficking. This situation is caused by some factors. One of them is that women are assumed as a particular stereotype role that can be laid easily. Women also like some jobs for example babysitter, dancer, or a singer in entertainment world. However, in fact, these kinds of jobs are actually smuggling sex commercial industry. Trafficking is defined as a human transfer (especially women and children), with or without their consent, within a country or internationality, for all forms of exploitative labor, not only prostitution and servile marriage, thus broadening the definition to encompass a much wider range of issues and abuses. Trafficking brings the bad effects for women and children, many things that bring them to the worst and unbeneficial condition, whether in social, psychological, or the children growth and their social interaction process. That is why; the efforts to eliminate children trafficking become one of the most important issues that must be solved immediately and seriously.Key Words: child trafficking, exploitation, and patriarchy